Cyclical transactions and wealth inequality - Jung Sakong (Federal Reserve Bank of Chicago, 2022)
Wealth is distributed more unevenly than income, and one contributing factor might be that richer households earn higher portfolio returns. I uncover one channel that causes portfolio returns to be increasing in wealth: Poorer households consistently buy risky assets in booms-when expected returns are low-and sell after a bust-when expected returns are high. Although time-varying expected returns are a robust empirical fact, theories are ambiguous on whether poorer or richer households engage in such cyclical trading patterns. I estimate the trading patterns for households across wealth levels, in the US housing market for 1988-2013. I interact housing ownership patterns from deeds records with household-level wealth, which I infer from merging owners' surnames with their name-based income in the 1940 full Census. The estimated dispersion in expected returns from this "buy-high-sell-low" channel is large: The interquartile-range difference is 60 basis points per year. The channel predicts that geographies with historically higher volatility will feature more wealth inequality than income inequality: I verify this implication in the data. These results suggest that a government policy intended to boost poorer households' wealth via homeownership can backfire if it ignores the status of house prices.
Keywords: D15; D31; E32; G11; R21; 330; Wealth inequality; business cycles; real estate asset; timing of transaction; wealth return